A fast estimation of distribution algorithm for dynamic fuzzy flexible job-shop scheduling problem. (September 2015) - Liu, Bojun; Fan, Yushun; Liu, Yi
Highlights: A "non-zero state fFJSP" is proposed. Dynamic job-shop scheduling problem is transformed for solving easily. We apply the estimation of distribution algorithm to solve this problem. Standardizing the solution vectors improves the efficiency of EDA. Bringing in the optimal solution's impact improves the precision of the solution. Abstract: Due to the complicated circumstances in workshop, most of the conventional scheduling algorithms fail to meet the requirements of instantaneity, complexity, and dynamicity in job-shop scheduling problems. Compared with the static algorithms, dynamic scheduling algorithms can better fulfill the requirements in real situations. Considering that both flexibility and fuzzy processing time are common in reality, this paper focuses on the dynamic flexible job-shop scheduling problem with fuzzy processing time (DfFJSP). By adopting a series of transforming procedures, the original DfFJSP is simplified as a traditional static fuzzy flexible job-shop problem, which is more suitable to take advantage of the existing algorithms. In this paper, estimation of distribution algorithm (EDA) is brought into address the post-transforming problem. An improved EDA is developed through making use of several elements omitted in original EDA, including the historical-optimal solution and the standardized solution vectors. The improved algorithm is named as fast estimation of distribution algorithm (fEDA) since it performs better in convergence speed and computation precision, compared with the original EDA. To sum up, the ingenious transformation and the effective fEDA algorithm provide an efficient and practical way to tackle the dynamic flexible fuzzy job-shop scheduling problem.